OPTIMIZATION OF CULTIVATION CONDITIONS FOR α-AMYLASE PRODUCER ACHROMOBACTER SP. 7а - К. В. Авдіюк; Л. Д. Варбанець; В. О. Іваниця (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2015)
Aim. The investigation of the optimal conditions for α-amylase production by Achromobacter sp. 7а. Methods. For studying the effect of different sources of carbon and nitrogen on the α-amylase biosynthesis the starch and sodium nitrate in a base culture medium were replaced by the various sources of nitrogen and carbohydrates in an amount equivalent to the total carbon content (44.4%) and nitrogen (16.5%) in the basic medium. α-Amylase activity was determined by iodometric method, protein content – by Lowry et al. The screening experiments were carried out to identify the significant mineral nutrients of base medium. Determination of optimal concentrations of carbon and nitrogen sources in the medium was carried out by bifactorial experiment on four levels. Results. It is established that the highest level of enzyme synthesis is observed on the 3 day of deep cultivation. It is shown that mix of malt with starch in the ratio 1:9 and nitrate of sodium are the optimum sources of carbon and nitrogen respectively, for the maximum enzyme producing. The optimum conditions of α-amylase biosynthesis were established: temperature is 28 °C, initial рН value 6.0, the volume of a nutrient medium is 100 ml, number of seed material 15% and intensity of hashing 210 rpm. Conclusions. The α-amylase production was rised fourfold as a result of bifactorial experiment and selection of optimum conditions of cultivation of Achromobacter sp. 7а.